Relation of maternal and cord blood serum ferritin. - Hussain, M A (1977)
Serum ferritin was measured in 51 term normal pregnant mothers and the corresponding cord blood samples. All of the mothers had received prophylactic oral iron and folate during pregnancy. The mean (+/-SD) maternal serum ferritin at the end of pregnancy was 58 +/- 42.9 microgram/l (range 16-201 microgram/l), compared to a mean of 183.2 +/- 61.2 microgram/l (range 62-313 microgram/l) in these newborns. No correlation was found between the serum ferritin of mothers and babies, nor between the serum ferritin and serum iron of mothers at the end of pregnancy or between these parameters in the newborn.